The Future of Participative Budgeting: A Bibliometric Analysis Using Vos Viewer - Aryan Danil Mirza. BR; Laili Fadhila Banuwa; Ghea Laili Putri Garien; Sartini (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to map the development, trends, and directions of research related to participative budgeting over the past four decades through a bibliometric analysis approach. Data were obtained from the Scopus database using the keyword “PARTICIPATIVE BUDGETING” for the period 1982–2025, resulting in 166 documents analyzed using VOSviewer and Publish or Perish software. The results show that the topic of particpative budgeting has evolved from a mere managerial mechanism to an interdisciplinary issue involving behavioral, ethical, and organizational governance dimensions. The most frequently appearing keywords include budgetary slack, honesty, performance, and managerial performance, which indicate a research focus on behavioral and managerial performance aspects. Geographically, the United States is the main center of research, followed by Germany, Australia, and Brazil, with increasing contributions from developing countries such as Indonesia. The field of study is dominated by Business, Management and Accounting, but is beginning to expand into Social Sciences and Computer Science. This research provides a theoretical contribution to strengthening the understanding of the role of participation in budgeting effectiveness and opens new research opportunities related to the integration of digital technology, organizational culture, and local context in particpative budgeting.